2009
DOI: 10.1177/154193120905301843
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of System Technology and Probability Type on Trust, Compliance, and Reliance

Abstract: The purpose of this research was to examine the effects of system technology (binary vs. likelihood) and probability type (false-alarm prone vs. miss-prone) on trust, compliance and reliance using a false alarm forgiving task. Onehundred university students participated in this study. Participants completed three simulated flight missions composed of two primary flight tasks and a secondary engine-monitoring task. During the first mission, participants performed the engine-monitoring task without the aid of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 13 publications
7
23
0
Order By: Relevance
“…Compliance refers to an operator responding in accordance with an alarm signal. Prior research shows that LAT tends to reduce compliance in FP systems (Bustamante, 2008;Stanton et al, 2009). Reliance and compliance do not appear to be completely independent of each other .…”
Section: Trust Reliance and Compliancementioning
confidence: 94%
See 2 more Smart Citations
“…Compliance refers to an operator responding in accordance with an alarm signal. Prior research shows that LAT tends to reduce compliance in FP systems (Bustamante, 2008;Stanton et al, 2009). Reliance and compliance do not appear to be completely independent of each other .…”
Section: Trust Reliance and Compliancementioning
confidence: 94%
“…Depending on the costs and benefits of a miss or a falsealarm in a given task, the task itself can be considered FP or MP. As an example of a FP task, Stanton, Ragsdale, and Bustamante (2009) evaluated the effects of LAT vs. BAT and FP vs. MP systems on trust, reliance, and compliance.…”
Section: Task Typementioning
confidence: 99%
See 1 more Smart Citation
“…Although some research has supported this hypothesis (Johnson, 2004), other research suggests that false alarms and misses have similar effects (Madhavan et al, 2006;Rovira & Parasuraman, 2010). Additionally, at least two studies have shown that participants trusted false-alarm-prone automation more than missprone automation (Davenport & Bustamante, 2010;Stanton, Ragsdale, & Bustamante, 2009). Overall, the specific impact that false alarms and misses have on trust likely depends on the negative consequences associated with each error type in a specific context.…”
Section: Learned Trustmentioning
confidence: 99%
“…If a user knows the principles of positioning calculation, their tolerance for positioning error could be higher than someone without this knowledge (Bell, et al, 2011). In addition, users having complete knowledge of the local environment tend to ignore the system's actual performance, which results in an inappropriate accuracy judgment (Stanton, Ragsdale, & Bustamante, 2009). Similarly, users tend to be critical of system performance when they are highly confident and have abundant knowledge of their surroundings (Kantowitz, Hanowski, & Kantowitz, 1997).…”
Section: System Accuracy Evaluationmentioning
confidence: 99%